ANALISIS RESIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN MENGGUNAKAN RISK ASSESSMENT PADA DOCK SYSTEM AIRBAGS DI PT. MERANTI NUSA BAHARI BALIKPAPAN - Noeryanto, Noeryanto; Siboro, Impol; Widodo, Agung Subaki (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Hazard analysis is part of the occupational safety and health program to find out the hazards that exist at each stage of the work carried out, so that control of the hazards and risks can be carried out to prevent work accidents. The purpose of this study is to find out what are the hazards that can be caused related to ship docking work using the airbag system and control of these hazards using the Hazard Identification Risk Assessment and Risk Control method. The research method used by the researcher is using a qualitative method sourced from AS/NZS 4360. The location and time of the research is PT. Meranti Nusa Bahari and research objects in the form of airbags, and workers during ship docking. The results obtained from the hazard analysis on ship docking work have 4 stages of the process using the Hazard Identification Risk Assessment and Risk Control method, with a value of 60% docking work in the Very high category, 44% in large category docking work and 20% acceptable docking work out of 15 dangers and risks in the ship docking work process using the airbag system. Keywords: Airbags, Hazard analysis, Ship docking